2009
DOI: 10.1016/j.ijhcs.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Adding critical sensibilities to domestic communication technologies

Abstract: This paper presents suggestions for a more pragmatic approach to the design of emerging and future domestic communication technologies, particularly technologies destined for the home that maybe deemed 'ubiquitous'. This is achieved through two critical reviews of a small number of social studies related to the design and use of existing and emerging communication technologies. The first review explores how existing, recent and emerging technologies are adopted within the domestic home and explores how social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Contact with parents via email was the third most frequently (2009) notes, the adoption of different forms of communications technology by families will likely be shaped both by family members' desire to maintain customary levels of contact and by a perceived need to enhance their existing communication practices. Future changes in family communication practices are likely to depend on the development of technologies that interface easily with other existing devices and are seen to somehow improve ways that family members communicate with one another (Bonner 2009). In our study, college students generally reported more frequent contact with parents via phone, text and other types of communications technology than reported previously (Gentzler et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contact with parents via email was the third most frequently (2009) notes, the adoption of different forms of communications technology by families will likely be shaped both by family members' desire to maintain customary levels of contact and by a perceived need to enhance their existing communication practices. Future changes in family communication practices are likely to depend on the development of technologies that interface easily with other existing devices and are seen to somehow improve ways that family members communicate with one another (Bonner 2009). In our study, college students generally reported more frequent contact with parents via phone, text and other types of communications technology than reported previously (Gentzler et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, students generally reported infrequent contact with parents via social media. However, digital technology is constantly changing, and it is unclear how different types of communications technology are being incorporated into the communication practices of families (Bonner 2009).…”
Section: Introductionmentioning
confidence: 99%
“…February 15-19, 2014, Baltimore, MD, USA ly different interpretations of the same technology [5]. However, as similar technologies are deployed in a variety of contexts, there may be a large enough sample to compensate for this variability and allow for between-study comparisons.…”
Section: Cscw 2014 • Telepresencementioning
confidence: 99%
“…Before implementing a technology, users will engage in a 'mental exercise of thinking and deciding' [30]. In the domestic context, parents act as technology advocates [4] whose choices ultimately bear on children's wellbeing. Parents acknowledge this responsibility by reflectively evaluating their motives when using technologies with their children [21].…”
Section: Parents Have Not Heard Of Location Trackingmentioning
confidence: 99%
“…We focused on parents in particular, as they are often the gatekeepers who determine what technologies are introduced in the family [4]. Given the little we know about the adoption of location tracking, adoption was measured using the exploratory framework proposed by Rogers' diffusion of innovations theory [30].…”
Section: Introductionmentioning
confidence: 99%